PERGAULAN REMAJA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Hernides Hernides (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
In this study, it examines how teenagers interact according to Islamic education. The purpose of this study was to determine the association of adolescents according to a review of Islamic education. This discussion uses descriptive analysis method, which is a method that addresses problems that exist in the present by using sharp analyzes based on the concepts of experts. Whereas in data collection the writer uses library research, namely by examining the books available in the library or other written works. Based on the results of the research, it shows that the association of youth in an Islamic perspective must always be guided by the Al-Quran and Hadith, because Islam has regulated the ways of having good morals and getting along properly. Because they have been recruited directly or indirectly to preach Islam, so that they become a young generation of Muslims who are ready to accept the mandate of shaming Islam. responsible for shaping the personality of the adolescent are parents or family, teachers and the community. Because the three of them are very important people in directing adolescents to form good morals by providing Islamic education based on the Al-Quran and Hadith